2010
DOI: 10.1590/s1413-86702010000600015
|View full text |Cite
|
Sign up to set email alerts
|

Native valve endocarditis and femoral embolism due to Granulicatella adiacens: a rare case report

Abstract: The fastidious Gram-positive cocci Granulicatella adiacens, previously known as nutritionally variant streptococci (NVS) are unusual but signifi cant cause of endocarditis due to increased mortality and morbidity. Diffi culties in reaching correct bacteriological identifi cation, increased resistance to beta-lactam antibiotics and macrolides and complicated clinical course have contributed to problems in management of cases of infective endocarditis caused by this bacterium. We present the fi rst Indian case o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 12 publications
0
4
0
1
Order By: Relevance
“…In most of the cases we reviewed, NVS were isolated from automated culture bottles. [5][6][7][8][9] However, on subculture from these positive bottles growth is generally either delayed or/and very faint. Colonies can be identified by satellitism around colonies of Staphylococcus aureus, typical Gram stain picture of pleomorphism and increased growth on thiol containing media.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In most of the cases we reviewed, NVS were isolated from automated culture bottles. [5][6][7][8][9] However, on subculture from these positive bottles growth is generally either delayed or/and very faint. Colonies can be identified by satellitism around colonies of Staphylococcus aureus, typical Gram stain picture of pleomorphism and increased growth on thiol containing media.…”
Section: Discussionmentioning
confidence: 99%
“…Vandana et al [5] IE Blood Mini API; disc diffusion AMP-(S) E-(S) (I/V) AMP and G Cured Swain and Otta [6] Carbuncle in Type-II diabetic patient…”
Section: Financial Support and Sponsorshipmentioning
confidence: 99%
“…Granulicatella spp. mogą być czynnikiem etiologicznym nawet w 5% IZW [1,37,55,56]. Częstość IZW o tej etiologii wynosi 44% na zastawce aortalnej, 38% mitralnej, 13% trójdzielnej, a w 13% jest to IZW wielozastawkowe [43,48,56].…”
Section: Paciorkowce O Szczególnych Wymaganiach Odżywczychunclassified
“…Other aetiologic agents include nutritionally variant streptococci (NVS) such as Abiotrophia and Granulicatella which account for about 5-6% of streptococcal endocarditis (Padmaja et al 2014;Giuliano et al 2012). Multiple case studies have found that endocarditis caused by Granulicatella sp has been associated with higher mortality rate (17%), higher rate for treatment failure (41%), and as high as 27% requirement for surgical intervention (Adam et al 2015;Vandana et al 2010). It is due to its fastidious Rahimi et al Egyptian Journal of Forensic Sciences (2022) 12:35 nature that it is frequently associated with negative blood culture, yielding in late bacteriological identification and increased antibiotic resistance to beta-lactam and macrolides (Vandana et al 2010).…”
Section: Introductionmentioning
confidence: 99%